2009
DOI: 10.1007/s00213-009-1589-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, psychomotor, and subjective effects of sodium oxybate and triazolam in healthy volunteers

Abstract: Rationale Illicit gamma-hydroxybutyrate (GHB) has received attention as a “date rape drug” that produces robust amnesia; however, there is little experimental evidence in support of GHB’s amnestic effects. Objectives This study compared the cognitive effects of GHB (sodium oxybate) with those of triazolam in healthy volunteers. Materials and methods Doses of sodium oxybate (1.125, 2.25, and 4.5 g/70 kg), triazolam (0.125, 0.25, and 0.5 mg/70 kg), and placebo were administered to 15 volunteers under repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
43
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 28 publications
10
43
3
Order By: Relevance
“…In addition, long-term therapy with GHB has been proposed for the treatment of alcohol withdrawal (Maremmani et al, 2001) with no reported problems of memory. However, acute doses of GHB may provoke some amnesia but far less important than hypnotic benzodiazepines (Carter et al, 2009). Our study shows that this amnestic effect of GHB is not persistent, even after chronic administration, confirming the clinical observations made in human patients.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, long-term therapy with GHB has been proposed for the treatment of alcohol withdrawal (Maremmani et al, 2001) with no reported problems of memory. However, acute doses of GHB may provoke some amnesia but far less important than hypnotic benzodiazepines (Carter et al, 2009). Our study shows that this amnestic effect of GHB is not persistent, even after chronic administration, confirming the clinical observations made in human patients.…”
Section: Discussionsupporting
confidence: 88%
“…Third, it is unlikely that there are larger doses of sodium oxybate that would result in much greater amnestic effects without loss of consciousness. This was found to be the case in a study that examined doses large enough to observe loss of consciousness (Carter et al 2006) and it is substantiated in the current study by the near maximal mean peak subjective effects ratings of drug effect and the significant decreases in balance at the largest dose of sodium oxybate studied (Carter et al 2009). Fourth, we agree and in fact, stated in the paper that studies designed to compare the effects of sodium oxybate and other drugs, such as ethanol, might be fruitful efforts.…”
supporting
confidence: 57%
“…The score was the number of words (out of 16) correctly recalled. For details, see (Carter et al 2009). …”
Section: Methodsmentioning
confidence: 99%